Citra tubuh Dan Kecenderungan Body Dysmorphic Disorder: Seberapa pentingkah penampilan fisik bagi remaja ? - Putri, Dwi Amalia; Nainggolan, Eben Ezer; Ul Haque, Sayidah Aulia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract This study aims to determine the relationship between body image and body dysmorphic disorder tendencies in teenagers in Surabaya. This study used a correlational quantitative research method. The participants in this study were all teenagers in Surabaya with the age range of 18-21 years. The number of participants in this study was 272 participants taken with reference to the Krejcie table with a confidence of 90%. The sample technique used was Accidental Sampling. The data analysis used is Spearman Rho. The results of this study showed a rho correlation coefficient value of -0.616 with a significance level of 0.000 (p≤0.05). Thus, there is a negative relationship between the two variables which shows that the higher the body image owned, the lower the tendency of body dysmorphic disorder, conversely the lower the body image owned, the higher the tendency of body dysmorphic disorder. Keywords: Body Dysmorphic Disorder; Body Image; Teenagers Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara body image dan kecenderungan body dysmorphic disorder pada remaja di Surabaya. Penelitian ini menggunakan metode penelitian kuantitatif korelasional. Partisipan dalam penelitian ini adalah seluhruh remaja di Surabaya dengan rentan usia 18-21 tahun. Jumlah partisipan pada penelitian ini adalah sebanyak 272 partisipan yang diambil dengan mengacu pada tabel krejcie dengan confidence sebesar 90%. Teknik sampel yang digunakan adalah Accidental Sampling. Analisis data yang digunakan adalah Spearman Rho. Hasil penelitian ini menunjukkan nilai koefisien korelasi rho sebesar -0,616 dengan taraf signifikansi 0,000 (p≤0,05). Dengan demikian, terdapat hubungan negatif antara dua variabel yang menunjukkan bahwa semakin tinggi body image yang dimiliki maka semakin rendah kecenderungan body dysmorphic disordernya, sebaliknya semakin rendah body image yang dimiliki maka semakin tinggi kecenderungan body dysmorphic disorder nya. Kata kunci: Body Dysmorphic Disorder; Body Image; Remaja